The Letter Wawu in Q.S. Al-Hasyr Verse 9 (Analysis of the Perspective of Nahwu Science) - Vira Rahmadini, Vira Rahmadini; Adisti Putri Aryani; Elsa Puspita (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2025)
The science of grammar is an important branch of Arabic grammar that functions as the main tool for understanding the structure and meaning of sentences in the Qur'an. One of the interesting syntactic elements to study is the letter Wawu (و), which has various functions depending on the context of its use. This study aims to specifically examine the various functions of the letter Wawu in QS. Al-Hasyr verse 9. This verse was chosen because it contains several forms of Wawu usage with different functions, such as the letter athof (connector), the letter hal (condition clarifier), and others. By using a syntactic analysis approach based on the rules of grammar, this study found that the letter Wawu in the verse not only functions as a connector between phrases or clauses, but also has an important role in forming meaning and clarifying the context of the sentence. The results of this study are expected to enrich the understanding of the function of letters in Arabic and contribute to the study of linguistics and interpretation of the Qur'an.